2021
DOI: 10.1108/ejm-04-2020-0255
|View full text |Cite
|
Sign up to set email alerts
|

The financial vulnerability trap: using latent transition analysis to explore the dynamics of consumers’ financial vulnerability over time

Abstract: Purpose The purpose of the paper is to examine how psychological characteristics predict membership of and transitions between states of higher vs lower financial vulnerability – and vice versa – over time. Design/methodology/approach This research uses a dynamic latent class model (latent transition analysis) to explore the dynamics of consumers’ financial vulnerability over time using longitudinal data obtained by repeatedly administering a measure of financial vulnerability. Findings This research finds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 69 publications
2
27
0
Order By: Relevance
“…Besides these individual risk factors, this study also found a range of psychological risk factors such as time preference, money management skills, consideration for future consequences, saving orientation, financial self-efficacy and so on particularly important. Hoffmann et al. (2020) added to these findings, as they reported that financial self-efficacy not only mediates the relationship of financial vulnerability with financial outcomes but also limits the consumer’s likelihood of experiencing financial vulnerability in the first place.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Besides these individual risk factors, this study also found a range of psychological risk factors such as time preference, money management skills, consideration for future consequences, saving orientation, financial self-efficacy and so on particularly important. Hoffmann et al. (2020) added to these findings, as they reported that financial self-efficacy not only mediates the relationship of financial vulnerability with financial outcomes but also limits the consumer’s likelihood of experiencing financial vulnerability in the first place.…”
Section: Literature Reviewmentioning
confidence: 99%
“…From a policymaking perspective, this could be viewed as a reassuring outcome; despite concerns about the limited controls in place to validate eligibility in the application process, the scheme appears to have been primarily accessed by individuals who genuinely needed financial support. At the same time, our findings should raise concerns about whether the scheme may further entrench individuals who were financially vulnerable to begin with ( Hoffmann et al, 2021 ).…”
Section: Discussionmentioning
confidence: 89%
“…Despite these limitations, our study contributes to the hitherto scarce literature on how to increase consumers' financial self‐efficacy and provides a set of actionable implications for policy makers and other practitioners on how to design and implement (more) effective interventions to financially empower (vulnerable) consumers (see e.g., Hoffmann et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%